Hi-C, a chromatin 3D structure technique advancing the functional genomics of immune cells - Liu, Ran; Xu, Ruitang; Yan, Siyu; Li, Peiyu; Jia, Changteng; Sun, Haoqiang; Sheng, Kaiwen; Wang, Yongjie; Zhang, Qi; Guo, Jiao; Xin, Xiangzheng; Li, Xinlan; et al. (Frontiers in Genetics, 2024)
The functional performance of immune cells relies on a complex transcriptional regulatory network. The three-dimensional structure of chromatin can affect chromatin status and gene expression patterns and plays an important regulatory role in gene transcription. Currently available techniques for studying chromatin spatial structure include chromatin conformation capture techniques and their derivatives, chromatin accessibility sequencing techniques, and others. Additionally, the recently emerged deep learning technology can be utilized as a tool to enhance the analysis of data. In this review, we elucidate the definition and significance of the three-dimensional chromatin structure, summarize the technologies available for studying it, and describe the research progress on the chromatin spatial structure of dendritic cells, macrophages, T cells, B cells, and neutrophils.